Computed tomography evaluation of palatal form in the transversal and sagittal fabrication process and the effect of first molar and canine crown angulations. (28th December 2019) - Yamen, Taljabini; Ulas, Oz
The purpose of this study was to investigate changes in the palatal form in patients treated with and without premolar extractions. A total of 40 patients who had undergone orthodontic treatment (extraction and non-extraction) were divided into two groups coequally. Retrospective records were collected at pretreatment and at bracket removal. Stone casts were scanned by cone-beam tomography; linear and angular measurements on the three-dimensional model were then performed for both the sagittal direction and the transverse direction. Paired t -tests for dependent samples were used to compare results within the same group, and t -tests for independent samples were used to compare results between groups. A p value less than 0.05 was considered statistically significant. The sagittal palatal form increased in the non-extraction group, whereas it decreased in the extraction group. There was a decrement in the transversal palatal form in both groups. There were no differences or changes in molar or canine crown angulation in the non-extraction group. Conversely, distal tipping of the upper right first molar and distal tipping and lingual movement of both left and right upper canines were observed in the extraction group.